Periodontitis and Accelerated Biological Aging: A Geroscience Approach - Baima, G.; Romandini, M.; Citterio, F.; Romano, F.; Aimetti, M. (Journal of dental research, 2022)
As the whole world is epidemically aging, the burden of periodontitis and tooth loss is becoming a major health concern. Growing meta-epidemiological data implicate chronic systemic inflammation/infection due to periodontitis as an independent risk factor for aging-related diseases and mortality. However, because people age differently, chronological age is not a reliable marker of an individual’s functional status. Recent advances in geroscience have shown that various biomarker signatures of biological aging are longitudinally associated with declined physical function, morbidity, and mortality due to major age-related diseases, including periodontitis. Here, we emphasize novel research developments bidirectionally linking periodontitis to accelerated biological aging. Using a composite biomarker age estimator, a striking increase in periodontitis and tooth loss was observed in subjects whose biological age at baseline was higher than their chronological age. Moreover, significantly shortened telomeres were encountered in populations affected by severe periodontitis. Second, we elucidate the cellular and molecular pillars of the aging process at the periodontal level. Accumulating evidence suggests that cellular senescence, stem cell exhaustion, and immunoaging are hallmarks of biological aging implicated in the impairment of periodontal homeostasis and the pathophysiology of periodontitis. Indeed, persistent bacteria-derived lipopolysaccharide stimulation influences cellular senescence in osteocytes, driving alveolar bone resorption. Moreover, inflammaging status induced by chronic hyperglycemia elevates the burden of senescent cells in gingival tissues, impairing their barrier function. Lastly, we reviewed a recent breakthrough in senotherapy to directly target the mechanisms of aging at the periodontal level. Physical exercise and intermittent fasting, together with natural compounds, senolytic drugs, and cell therapy, are increasingly being evaluated to rejuvenate the oral cavity. Following these innovations in geroscience, further advancements could provide oral clinicians the chance to intercept biological aging when still “subclinical” and set interventions for halting or delaying the trajectory toward aging-related diseases while patients are still chronologically young.